KONSTRUKSI SOSIAL PELAYANAN KESEHATAN BERBASIS TAT TWAM ASI - I Wayan Suwirja; Ni Wayan Widhiasthini (LPPM STIKES KENDAL, 2019)
ABSTRACT Health service standards that can improve service quality and customer satisfaction are health services that are easier, faster, and more practical. To realize excellent service standards, Sanglah General Hospital Denpasar makes